ChemInform Abstract: Synthesis of Terminal Allenes Through Copper‐Mediated Cross‐Coupling of Ethyne with N‐Tosylhydrazones or α‐Diazoesters. Issue 22 (15th May 2015) - Ye, Fei; Wang, Chengpeng; Ma, Xiaoshen; Hossain, Mohammad Lokman; Xia, Ying; Zhang, Yan; Wang, Jianbo
Abstract: The required N‐tosylhydrazones (I) and (V) are easily prepared from the corresponding ketones and aldehydes and they are stable and easy to purify.